Effects of fitspiration on believability and intention to exercise - Berry, Tanya R.; Locke, Sean; Ori, Elaine M. (Frontiers in Psychology, 2023)
Introduction Although Fitspiration is purportedly intended to motivate people to be fit and healthy, a body of research has demonstrated negative effects of these media in men and women. Understanding mechanisms can help create more targeted interventions aimed at mitigating the negative effects of Fitspiration. This research examined if selected implicitly or explicitly measured constructs moderated or mediated the effects of Fitspiration. The purposes were to examine the believability (finding the media truthful) of Fitspiration (study one; data from 139 women and 125 men aged 18–33 years were analyzed), the effects of Fitspiration on exercise intention (study two; data from 195 women and 173 men aged 18–30 years were analyzed), and whether these effects were moderated by exercise-related cognitive errors (negatively biased perception of exercise) or mediated by implicit (evaluative responses to stimuli) or explicit (reasoned evaluation of stimuli) attitudes. Methods In two separate studies, self-identified men and women first completed a measure of exercise-related cognitive errors, then viewed gender-specific Fitspiration media, followed by measures of implicit attitudes, explicit attitudes, believability, and demographics. In study two, participants were randomly assigned to Fitspiration or control media conditions and also completed measures of fitspiration-related cognitive errors and intention to exercise. In the first study, one model was tested for each gender sample. It was hypothesized that implicit and explicit attitudes would be positively related to believability, and that exercise-related cognitive errors would moderate these relationships. In study two, separate models were tested with exercise-related or Fitspiration-related cognitive errors as the moderators with each gender sample. It was hypothesized that implicit attitudes, explicit attitudes, and believability would be positively related to intention, that the control media would lead to greater intention to exercise than the Fitspiration media, and that exercise-related cognitive errors and Fitspiration-related cognitive errors would moderate these relationships. Results The majority of hypothesized relationships were not supported. A negative relationship between exercise-related cognitive errors and believability was found. Discussion Overall, these studies identify and exclude factors that predict Fitspiration believability and the role that factors such as cognitive errors and attitudes may play in that.